Black-to-transparent electrochromic capacitive windows based on conjugated polymers. Issue 29 (13th July 2021) - Han, Minsu; Cho, Cheol Hyun; Jang, Hwandong; Kim, Eunkyoung
Abstract : A black-to-transparent electrochromic (EC) capacitive window was explored for the first time through the combination of a dual EC polymer and capacitive polymer layer, to provide a high transparency (>75%) and large color contrast (65%). Abstract : A black-to-transparent electrochromic capacitive window (BTECCW) is explored through the combination of a dual electrochromic polymer (ECP) and a capacitive polymer layer. A black-colored polymer (PEB1) is obtained using 3, 3-bis((2-ethylhexyloxy)methyl)-3, 4-dihydro-2 H -thieno[3, 4- b ][1, 4]dioxepine and 4, 7-dibromo-2, 1, 3-benzothiadiazole monomer, through a concerted metalation–deprotonation pathway. A high color contrast ECP layer is obtained by coating a poly(3, 3-bis(bromomethyl)-3, 4-dihydro-2 H -thieno[3, 4- b ][1, 4]dioxepine) (PR-Br) layer on ITO glass and then coating PEB1 over PR-Br to form a dual ECP layer. A porous and ordered polyaniline film is grown from aniline interfaced-graphene flakes, to provide a capacitive layer with a high surface area (31.8 m 2 g −1 ) and electrical conductivity (25 S cm −1 ). The combination of the above ECP and capacitive layer affords a highly transparent (>75%) and a large color contrast (65%) BTECCW, which shows a large energy density (26.9 W h kg −1 ) and a power density (23.9 kW kg −1 ). The redox energy of the BTECCW is stored and used to fuel an electronic clock and R-LED. These results confirm that BTECCWs can function as a battery for energy storage while being a smart window that can control the blocking and transmission of visible light. A 10 × 10 cm 2 size BTECCW is demonstrated, to feature the scalability of the electrochromic capacitive window.